La brecha en Inteligencia Artificial entre los países de América Latina: ¿se replican las brechas digitales de Internet? (Law, State and Telecommunications Review, 2026)
[Purpose] The objective is to analyze the differences among Latin American countries in the adoption and implementation of Artificial Intelligence (AI) and to relate this AI gap to the existing digital divide in Internet access.[Methodology/approach/design] A k-means cluster analysis is conducted to classify and differentiate the countries in the region based on several dimensions of the Latin American Artificial Intelligence Index (ILIA), together with international data on connectivity, Information and Communication Technologies, and cybersecurity.[Findings] Three country clusters are identified: AI-Advanced, AI-Emerging, and AI-Lagging. Brazil, Chile, and Uruguay form the advanced group, characterized by high levels of Internet connectivity (narrow Internet digital divides), robust AI infrastructure, strong AI governance, and abundant talent. The emerging countries differ from the advanced ones mainly in AI governance and e-commerce (wider Internet appropriation gap). The largest group consists of AI-lagging countries, which show lower levels across all variables. The clusters also reflect significant differences in innovation and human development, though not in GDP. Countries with high AI infrastructure have higher GDP than those with low AI infrastructure.[Practical implications] The country classification serves as a tool for political and strategic decision-making. It enables more efficient policies to promote AI and its implementation. AI-lagging countries can strengthen their digital foundations and actively foster AI adoption through collective policies and strategies tailored to their profile. In these countries, AI amplifies the pre-existing Internet digital divide. Transitioning from emerging to advanced status requires institutional changes and investment in talent.[Originality/value] This study recognizes the existence of an AI gap among Latin American countries by identifying, on one hand, the AI-leading nations and, on the other, the emerging and lagging ones. Furthermore, it links this AI inequality or gap to the Internet digital divide. AI tends to generate new inequalities due to its dependence on advanced infrastructure, specialized knowledge, and control over data.